Single-walled carbon nanotubes sensors: Preparation and bio-application advances - Xiaotong Chen; Difan Wang; Wenshuo Ding; Hengchang Zang; Lian Li (Pharmaceutical Science Advances)
Molecular recognition and detection are the main concerns in the field of biological analysis because they can be affected by various factors. Single-walled carbon nanotube (SWCNTs)-based optical biosensors have been applied in this field owing to their high sensitivity, good fluorescence stability, and tissue transparency. Purification of single-chiral SWCNTs and surface functionalization of SWCNTs are effective strategies for achieving real-time monitoring and high-throughput screening of biological analytes. Combining these technologies with microfluidic platforms and machine learning algorithms further broadens the application areas of sensors and enhances their analytical performance and usefulness in complex biological systems. Therefore, this review first discusses the preparation methods for single-chiral SWCNTs in recent years and introduces covalent and non-covalent functionalization techniques for SWCNTs, including oligonucleotide chains, peptides, and surfactant modifications. Subsequently, we systematically evaluate the applications of functionalized SWCNT biosensors for recognizing small molecules, including gas phase composition, neurotransmitters, and reactive oxygen species. These biosensors have been shown to have high sensitivity and specificity in the detection of a wide range of small molecules, offering a wide range of possibilities for analyzing volatile organic compounds, signaling molecules, and reactive oxygen species within biological systems, and providing new ways of gaining insights into the complex mechanisms of disease progression. Finally, we have analyzed the ability of SWCNT biosensors to recognize biomolecules in various categories, including proteins, nucleic acids, and lipids. Using these sensors for clinical disease diagnosis improves the accuracy and timeliness of diagnosis and opens up new ways to improve patients' prognosis and quality of life. We believe that SWCNT biosensors have great potential for future development in biomedicine.